THE HISTORY OF THE DEVELOPMENT OF ISLAM BY MALIM SALAWET IN MANDAILING NATAL IN 1810-1870 A.D: SEJARAH PENGEMBANGAN ISLAM OLEH MALIM SALAWET DI MANDAILING NATAL PADA TAHUN 1810-1870M - Hasibuan, fadhillah ani; Achiriah; Solihah Titin Sumanti (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The aim of this research is to describe the history and development of the Islamic religion in Mandailing Natal. The research method used is historical research methods. Research subjects were grouped into two groups, namely primary and secondary data sources. Primary data sources include handwritten Al-Quran, books written by his descendants and visits to Malim Salawet and several of his descendants, while secondary data sources were obtained from several libraries. Data collection techniques: observation, interviews and documentation. Data analysis uses: data reduction, data presentation, and drawing conclusions. Based on the research results obtained, it can be concluded that the first Muslims who entered and developed in Mandailing Natal Regency were from Pasaman, Minang Kabau, West Sumatra, and they came from Natal which was the original Islamic settlement in Mandailing Natal.